Detection of Helicobacterpylori Antigens among Patients with Gastroenteritis in Erbil City, Iraq - Pshtewan D. Majeed; Karim J. S. Khoshnaw; Hussein M. Abdullah (Polytechnic Journal)
Helicobacter pylori is a significant pathogen of the gastrointestinal tract infection connected with gastritis, peptic ulcers, and gastric carcinoma. Its infection influence more than half of the world’s inhabitants. This study aims to reveal the prevalence rate of H. pylori infection among patients with gastroenteritis and to investigate the risk factors such as age, gender, residency, blood group and rhesus factors related to this infection in Erbil city. Of 300 stool specimens from patients presenting with gastroenteritis who were admitted to Rizgary Teaching Hospital, Erbil, Iraq, from September 2018 to February 2019 were collected and screened for the presence of H. pylori antigens using rapid immunochromatographic assay (Camp Medica Group, Bucharest, Romania). A questionnaire sheet was prepared and used for each study subject. Of 300 samples examined, H. pylori were detected in 79 samples (26.33%). The highest rate of H. pylori infection was founded among the age group 21–30 years, but there were no significant differences between them (P > 0.05). A significant relationship between H. pylori infection and gender (male 19.05% and female 33.33%) was recorded (P < 0.05). There was a significant association between H. pylori infection and ABO blood group among patients (P < 0.05), but there is no significant association between H. pylori infection and the type of rhesus factor (P > 0.05) that H. pylori infection was higher in rhesus factor negative compared to rhesus factor positive. The prevalence was significantly higher among rural area (55.56%) than urban area (23.44%) (P < 0.05). We concluded that the spread of H. pylori positive rate was high among patients with gastroenteritis in Erbil city. The great prevalence of H. pylori was founded in the patients with O blood group, urban area, and females. There was no significant association between H. pylori infection and age groups and rhesus factor.